2015
DOI: 10.1007/s11104-015-2586-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen fertiliser use efficiency of wheat seedlings grown in soils from contrasting tillage systems.

Abstract: Aims This paper assessed the effect that the vertical stratification of nutrients in conservation cropping systems of Australia has on phosphorus (P) and nitrogen (N) fertiliser use efficiency. Methods Intact soil cores from two long-term tillage experiments, located on a Vertosol and on a Calcarosol were used to assess if tillage system (zero tillage -ZT vs conventional tillage -CT) and soil water influence fertiliser use efficiency (using 33 P and 15 N) of wheat under controlled growth conditions. Results Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A central assumption of the ILT is a homogeneous labeling of the plant-available soil nutrient pool, so that any dilution of the label observed in the fertilized treatment compared with the non-fertilized reference treatment is assigned to nutrient release from the applied fertilizer (Fardeau, Guiraud, & Marol, 1996;Hood-Nowotny, 2008). Isotopic techniques have been used to determine the fate of N or P added with mineral and/or organic fertilizers both in temperate (Armstrong et al, 2015) and in tropical soils (Bado, Bationo, Lompo, Cescas, & Sedogo, 2007;Douxchamps et al, 2011). In temperate Australian soils, Armstrong et al (2015) concurrently studied the use efficiency of water-soluble mineral P and N by wheat using the 15 N and 33 P direct double labeling technique.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…A central assumption of the ILT is a homogeneous labeling of the plant-available soil nutrient pool, so that any dilution of the label observed in the fertilized treatment compared with the non-fertilized reference treatment is assigned to nutrient release from the applied fertilizer (Fardeau, Guiraud, & Marol, 1996;Hood-Nowotny, 2008). Isotopic techniques have been used to determine the fate of N or P added with mineral and/or organic fertilizers both in temperate (Armstrong et al, 2015) and in tropical soils (Bado, Bationo, Lompo, Cescas, & Sedogo, 2007;Douxchamps et al, 2011). In temperate Australian soils, Armstrong et al (2015) concurrently studied the use efficiency of water-soluble mineral P and N by wheat using the 15 N and 33 P direct double labeling technique.…”
Section: Core Ideasmentioning
confidence: 99%
“…Isotopic techniques have been used to determine the fate of N or P added with mineral and/or organic fertilizers both in temperate (Armstrong et al., 2015) and in tropical soils (Bado, Bationo, Lompo, Cescas, & Sedogo, 2007; Douxchamps et al., 2011). In temperate Australian soils, Armstrong et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total concentration of Fe and P in the XGO-Fe(III) and XGO-Fe-P samples were determined using an open vessel concentrated acid digestion procedure (3.75: 1.25: 1 mL of concentrated HCl: HNO 3 : HClO 4 ). 21,22 The samples (~0.1 g) were added into a glass reflux tube with 6 mL of concentrated acids mixture and digested on a heating block at 140 °C for 6 h. After digestion, samples were filtered using 0.45 μm syringe filters (Sartorius) and analysed for total Fe and P concentrations using inductively coupled plasma-optical emission spectroscopy (ICP-OES) (Spectro, Kleve, Germany). The amount of Fe, or Fe and P, loaded onto XGO-Fe(III) and XGO-Fe(III)-P composites (U), was calculated using equation (1):…”
Section: Total Fe and P Concentration In Go-fe-p Compositesmentioning
confidence: 99%
“…Longer term soil P fertility benefits, from the contribution of P rich BG plant residues such as those of canola, may indirectly arise as a result of the concomitant increase in soil P status since it has been suggested that increasing P status of a soil can induce greater P mineralisation (Thibaud et al 1988) as well as reduce residual and current fertiliser P sorption (Barrow and Debnath 2014). It has been said that another longer term potential value of BG P in root systems is that it will naturally be distributed to some depth through the soil profile (Read and Campbell 1981), in contrast to the stratification of P that tends to occur with retention of shoot residues on the surface under no-till management (Deubel et al 2011) and applications of P fertiliser at shallow depths (~5 cm), and this may be advantageous for crops in dry land systems where the topsoil can be periodically too dry for nutrient uptake to occur (Armstrong et al 2015). However, our study indicates that a large proportion of BG P is concentrated in the top 0.1m of soil depth.…”
Section: Modelling Undertaken Bymentioning
confidence: 99%